Analisis Kelayakan Pupuk dari Limbah Serai Wangi dengan Pendekatan Ekonomi Sirkular - Meysa Nazila Maratul Qamilah; Dika Supyandi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Solid waste from citronella distillation has great potential to be reused within a circular economy system to reduce pollution and increase the added value of agricultural products. This study aims to analyze the financial and non-financial feasibility of processing citronella solid waste into compost fertilizer at the Harapan Sejahtera Farmers Group, Mekarlaksana Village, Ciparay District, Bandung Regency. A qualitative approach was employed using a case study method through interviews, observations, and documentation, along with financial analysis covering fixed costs, variable costs, total production costs, revenue, net income, and the R/C ratio. The results show that the processing of citronella solid waste produces 33 sacks of compost per production cycle with a total cost of IDR 1,166,925 and revenue of IDR 1,320,000, resulting in a profit of IDR 153,075 and an R/C ratio of 1.13. This indicates that the business is financially feasible. From a non-financial perspective, this activity has the potential to create new employment opportunities, support sustainable agricultural practices, and contribute to environmentally friendly waste management. With strong institutional, technical, and social support, compost fertilizer production from citronella waste is considered feasible to be developed as part of the implementation of a circular economy in the agribusiness sector.